Introgression from genetically modified plants into wild relatives (CABI, 2004)
Introgression is the incorporation of a gene from one organism complex into another as a result of hybridization. A major concern with the use of genetically modified (GM) plants is the unintentional spread of the new genes from cultivated plants to their wild relatives and the subsequent impacts on the ecology of wild plants and their associated flora and fauna. The book reviews these issues, focusing on the ecological and evolutionary effects of introducing GM cultivars. It presents a summary of the current knowledge state of crop-wild relatives hybridization and introgression, and the measurement and prediction of their consequences. As a result it represents a major contribution to the debate about the risks of GM crops and measures, such as post commercialization monitoring, required to determine the longer term impacts of GM crops on ecosystems. The book presents edited and revised presentations given at a conference of the same name, organized in January 2003 by the University of Amsterdam (Netherlands) and the Robert Koch Institute (Germany), on behalf of the European Science Foundation funded programme for Assessment of the Impacts of Genetically Modified Plants (AIGM).